IMPROVING TEACHERS' CAPABILITIES IN UTILIZING THE SCHOOL ENVIRONMENT AS A LEARNING SOURCE THROUGH TEACHER DISCUSSION AT THE STATE SCHOOL OF CARANGWULUNG III SUB-DISTRICT WONOSALAM, JOMBANG REGENCY - Biyanto Biyanto (Program Studi Pendidikan Guru Sekolah Dasar, 2021)
The purpose of this study was to determine the teacher's efforts to improve performance in utilizing the school environment as a learning resource and whether discussions could improve teacher performance in utilizing the school environment as a learning resource at SDN Carangwulung III, Wonosalam District, Jombang Regency. This research is an action research that aims to improve teacher performance in utilizing the school environment as a learning resource through discussions at SDN Carangwulung III Wonosalam District. The subjects of this study were teachers of SDN Carangwulung III, Wonosalam District, Jombang Regency, totaling 8 people, consisting of 5 PNS teachers, and 3 non-permanent teachers. Meanwhile, the object of research is the teacher's performance in utilizing the school environment as a learning resource. Implementation process Utilizing the school environment as a learning resource starts with initial supervision. Initial supervision is carried out to identify problems that exist in the determination. There was an increase in the readiness of participants in the discussion activities. The teachers of SDN Carangwulung III, Wonosalam District gave a very positive response to the activity of utilizing the school environment as a learning resource through discussion.